Lack of diagnosis leading to death of a cat with Aelurostrongylus abstrusus: Case report - Matsui, A.; Luzzi, M. C.; Ferreira, V. A.; Santos, P. C. D. dos; Moreira, P. R. R.; André, M. R. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Veterinary negligence and malpractice in Brazil are punished not only by administrative instances via Veterinarian´s Code of Ethics, CFMV resolution nº 875/2007, chapter V, Federal Council of Veterinary Medicine (BRASIL, 2007), but by juridical instances: Article 927 from Brazilian Civil Code (BRASIL, 2016), and Article 14 of Brazilian Consumer Protection Code (BRASIL, 2017). Therefore, it is extremely important and desirable that the vets have knowledge about the laws that conduct their practices and have prudence while dealing with the patients and the owners. A hasty action cannot only ruin an entire career for vets, but can cost the animal’s life. A vet has to certify not committing these mistakes, mainly in diagnosis and in procedures that deal directly with the patient’s life, like anesthesia, surgery and emergency.